Antibody-mediated immunotherapy against chronic hepatitis B virus infection - Ying Gao; Tian-Ying Zhang; Quan Yuan; Ning-Shao Xia (Taylor & Francis Group, 2017)
The currently available drugs to treat hepatitis B virus (HBV) infection include interferons and nucleos(t)ide analogs, which can only induce disease remission and are inefficient for the functional cure of patients with chronic HBV infection (CHB). Since high titers of circulating hepatitis B surface antigen (HBsAg) may be essential to exhaust the host anti-HBV immune response and they cannot be significantly reduced by current drugs, new antiviral strategies aiming to suppress serum hepatitis B surface antigen (HBsAg) could help restore virus-specific immune responses and promote the eradication of the virus. As an alternative strategy, immunotherapy with HBsAg-specific antibodies has shown some direct HBsAg suppression effects in several preclinical and clinical trial studies. However, most described previously HBsAg-specific antibodies only had very short-term HBsAg suppression effects in CHB patients and animal models mimicking persistent HBV infection. More-potent antibodies with long-lasting HBsAg clearance effects are required for the development of the clinical application of antibody-mediated immunotherapy for CHB treatment. Our recent study described a novel mAb E6F6 that targets a unique epitope on HBsAg. It could durably suppress the levels of HBsAg and HBV DNA via Fcγ receptor-dependent phagocytosis in vivo. In this commentary, we summarize the current research progress, including the therapeutic roles and mechanisms of antibody-mediated HBV clearance as well as the epitope-determined therapeutic potency of the antibody. These insights may provide some clues and guidance to facilitate the development of therapeutic antibodies against persistent viral infection.